Accessible active sites activated by nano cobalt antimony oxide @ carbon nanotube composite electrocatalyst for highly enhanced hydrogen evolution reaction. (8th March 2023) - Chen, Chen; Wen, Mingyue; Cheng, Ting; Tian, Yuan; Zhang, Xiao; Hou, Baoxuan
Abstract: The electrochemical hydrogen evolution reaction (HER) was one of new energy development strategies with clean, efficient and renewable characteristics, and electrocatalysts play a crucial role in HER technology. Herein, a composite material (CSO@0.5CNT) derived from the combination of nano cobalt antimony oxide (CSO) with carbon nanotubes (CNT) through hydrothermal reaction, in which the nanoparticles of CSO were closely compounded on the surface of CNT, could be a highly efficient electrocatalyst for HER in 1 M KOH. The binary composite electrocatalyst of CSO and CNT reduced the internal resistance, promoted the charge transfer, exhibited a large electrochemical active area, and obtained the lower overpotential, with 155 mV at 10 mA/cm 2 current density. Moreover, such a CSO@0.5CNT electrocatalyst displayed a small Tafel slope of 86.5 mV dec −1, excellent catalytic activity and extraordinary long-term structural stability after 30 h and 3000 CV cycles. Furthermore, the electrocatalytic mechanism revealed by Density Functional Theory (DFT) calculation proved that, the decomposition of H2 O molecules was the control step of the whole HER, and the superior electron transport ability of CNT was favorable to the improvement of electrocatalytic performance. Benefitting from accessible active sites on carbon nanotube (C atom) and CSO (Co atom), the composite electrocatalyst of CSO@0.5CNT displayed synergistic effect for electrocatalytic HER properties, and that was the main mechanism for significantly improving the electrocatalytic activities. Our work provides a novel strategy towards high-efficiency electrocatalysts for hydrogen evolution reaction. Graphical abstract: Image 1 Highlights: A composite electrocatalyst (CSO@0.5CNT) was prepared and studied comprehensively. The composite exhibited excellent electrocatalytic activity for HER, with low overpotential of 155 mV. Accessible active sites on carbon nanotube and CSO were contributed to the electrocatalytic HER properties. The composite displayed extraordinary long-term stability after 30 h and 3000 CV cycles.